Where the Wild Things Go: Tourism and Ethnic Longing in the Theatre of Rodolfo Santana - Vicky Unruh (Studies in 20th & 21st Century Literature, 2008)
Tapping into the performative intricacies of tourist activity and showcasing the negotiations of performed ethnicity in the implicit contrasts between tourists and the people they travel to see, Latin American and U.S. Latino theatre artists use the tourist character or theme to investigate the cultural negotiations marking contemporary social life. This work parallels critical theory that investigates the tourist as an improvisatory player in trans-regional interactions and unpacks the tourist-“native” binary to revise conceptions of people and cultures that travel. As exemplified in two plays by Rodolfo Santana (Venezuela), artists deploy the tourist theme to critique culturalism, that is, to use the term coined by Arjun Appadurai, “identity politics at the level of the nation-state” (15). Santana’s plays Mirando al tendido (1992) and Influencia turística en la inclinación de la Torre de Pisa (1996) highlight the interaction of tourism with its designated other, the ethnic, to critique the concept of abolengo, or nation-based ancestry or blood-line, as the authenticating mechanism of a particular cultural practice or group. Santana’s work—along with that of his cohort—also proposes that staging tourism harbors insights into the everyday that might generate more salutary social arrangements.
Keywords: tourist activity; tourism; ethnicity; Latin America; U.S. Latino; trans-regional interactions; Rodolfo Santana; cultural critique; Mirando al tendido; influencia turística en la inclinación de la Torre de Pisa; other; abolengo